Liquid crystal polymer composition

The liquid crystal polymer composition, formulated with glass-based fillers and functional group-containing olefin resin, addresses the issue of heat shock resistance in insert molded products, ensuring mechanical integrity and fluidity under varying temperatures.

JP2025053837APending Publication Date: 2025-04-07UENO PHARMA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023162903
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing liquid crystal polymer compositions lack sufficient heat shock resistance, leading to breakdowns in insert molded products under repeated heating and cooling cycles, particularly at stress-concentrated areas and weld lines.

Method used

A liquid crystal polymer composition is developed by blending 100 parts by mass of liquid crystal polymer with 10 to 60 parts by mass of glass-based filler, such as glass spheres or fibers, and 0.5 to 25 parts by mass of functional group-containing olefin resin, maintaining mechanical strength and fluidity while enhancing heat shock resistance.

Benefits of technology

The composition achieves excellent heat shock resistance, maintaining mechanical strength and fluidity, and effectively preventing breakdowns in insert molded products even under extreme temperature fluctuations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025053837000022
    Figure 2025053837000022
  • Figure 2025053837000023
    Figure 2025053837000023
  • Figure 2025053837000001
    Figure 2025053837000001
Patent Text Reader

Abstract

To provide a liquid crystal polymer composition having excellent heat shock resistance while maintaining mechanical strength, flowability, and other properties of liquid crystal polymers.SOLUTION: The present invention relates to a liquid crystal polymer composition comprising: 100 pts.mass of a liquid crystal polymer, 10 to 60 pts.mass of a glass-based filler, and 0.5 to 25 pts.mass of a functional group-containing olefin resin, wherein the glass-based filler is one or more selected from the group consisting of glass spheres and glass fibers having an aspect ratio of 10 or less, and the ratio of tensile elongation to tensile modulus is 0.6 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polymer composition having excellent heat shock resistance. [Background technology]

[0002] Liquid crystal polymers are excellent in various properties such as electrical properties such as heat resistance, chemical resistance, and tracking resistance, mechanical properties, and moldability. Therefore, liquid crystal polymers are widely used as engineering plastics in electronic components such as housings and connectors for electronic devices, automobile components, etc. These components are often insert molded products in which an insert member made of metal or the like is placed in a mold, and the mold is filled with liquid crystal polymer to integrally mold the metal or the like and the liquid crystal polymer.

[0003] However, because the thermal expansion and contraction rates of the metals and liquid crystal polymers that make up the insert molded product are significantly different from each other due to temperature changes, in an environment where heating and cooling are repeated, the insert molded product may be destroyed by temperature changes during use, which is called heat shock destruction. Heat shock destruction is particularly likely to occur in places where stress is likely to concentrate in the molded product, such as sharp corners of the insert member and places where there is a large change in thickness (especially thin parts), and places where the strength is lower than other parts, such as weld lines, which are the seams where the liquid crystal polymer splits from the insert member inside the mold during insert molding, goes around the insert member, and then joins again. For this reason, liquid crystal polymers are required to have heat shock resistance.

[0004] In order to improve the heat shock resistance of liquid crystal polymers, a technique has been proposed in which a thermally conductive filler such as carbon fiber is incorporated into the liquid crystal polymer (Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-83239 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the method described in Patent Document 1 is not sufficient in improving the heat shock resistance of liquid crystal polymers, and further improvement is desired.

[0007] An object of the present invention is to provide a liquid crystal polymer composition which has excellent heat shock resistance while maintaining the properties of a liquid crystal polymer such as mechanical strength and fluidity. [Means for solving the problem]

[0008] In view of the above problems, the inventors conducted intensive research and discovered that the heat shock resistance of liquid crystal polymers can be significantly improved by blending a specific glass-based filler and a functional group-containing olefin resin in a specified ratio with the liquid crystal polymer, thereby completing the present invention.

[0009] That is, the present invention includes the following preferred embodiments. [1] A liquid crystal polymer composition comprising 100 parts by mass of a liquid crystal polymer, 10 to 60 parts by mass of a glass-based filler, and 0.5 to 25 parts by mass of a functional group-containing olefin-based resin, wherein the glass-based filler is at least one type selected from the group consisting of glass spheres and glass fibers having an aspect ratio of 10 or less, and wherein the ratio of tensile elongation / tensile modulus of elasticity is 0.6 or more. [2] The liquid crystal polymer is represented by the formula (I) and the formula (II) [ka] The liquid crystal polymer composition according to [1], which is a liquid crystal polyester resin containing a repeating unit represented by the following formula: [3] The liquid crystal polymer is represented by the formula (I) and the formula (II) [ka] The liquid crystal polymer composition according to [1], which is a liquid crystal polyester resin composed of a repeating unit represented by the following formula: [4] The liquid crystal polymer is represented by the formula (I) to the formula (IV). [ka] [In the formula, Ar1 and Ar2 each represent a divalent aromatic group.] The liquid crystal polymer composition according to [1], which is a wholly aromatic liquid crystal polyester resin containing a repeating unit represented by the following formula: [5] The repeating units represented by the formulae (III) to (IV) are each independently represented by the formulae (1) to (4). [ka] The liquid crystal polymer composition according to [4], wherein each of the repeating units is one or more types selected from aromatic groups represented by the following formula: [6] The liquid crystal polymer composition according to [5], wherein the repeating unit represented by formula (III) is a repeating unit in which Ar1 is an aromatic group represented by formula (1), and the repeating unit represented by formula (IV) is a repeating unit in which Ar2 is an aromatic group represented by formula (1) and / or an aromatic group represented by formula (3). [7] The liquid crystal polymer composition according to any one of [1] to [6], wherein the glass spheres are glass beads and / or glass balloons. [8] The liquid crystal polymer composition according to any one of [1] to [7], having a tensile elongation of 3.0 to 7.5%. [9] The liquid crystal polymer composition according to any one of [1] to [8], having a tensile modulus of elasticity of 4.5 to 10.5 GPa.

[10] The liquid crystal polymer composition according to any one of [1] to [9], further comprising 1 to 50 parts by mass of a plate-like filler.

[11] The liquid crystal polymer composition according to

[10] , wherein the plate-like filler is mica and / or talc.

[12] A molded article made of the liquid crystal polymer composition according to any one of [1] to

[11] .

[13] The molded article according to

[12] , which is a part constituting one type selected from the group consisting of a connector, a switch, a relay, a capacitor, a coil, a transformer and an antenna.

[14] An insert molding comprising the liquid crystal polymer composition according to any one of [1] to

[11] and a metal. Effect of the Invention

[0010] The liquid crystal polymer composition of the present invention has excellent heat shock resistance while maintaining the properties of liquid crystal polymers such as mechanical strength and fluidity, and is therefore suitably used for, for example, insert moldings. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a perspective view showing an insert member used in a heat shock resistance test. [Diagram 2] FIG. 2 is a perspective view showing an insert molded article used in a heat shock resistance test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The liquid crystal polymer (hereinafter also referred to as LCP) used in the liquid crystal polymer composition of the present invention is a polyester or polyesteramide that forms an anisotropic molten phase, and is not particularly limited as long as it is what is called a thermotropic liquid crystal polyester or a thermotropic liquid crystal polyesteramide in the relevant technical field.

[0013] The nature of the anisotropic molten phase can be confirmed by conventional polarized light examination using crossed polarizers. More specifically, the anisotropic molten phase can be confirmed by observing the sample on a Leitz hot stage under nitrogen atmosphere at 40x magnification using a Leitz polarized microscope. The liquid crystal polymers of the present invention are optically anisotropic, i.e., transmit light when examined between crossed polarizers. If the sample is optically anisotropic, polarized light will be transmitted even when it is stationary.

[0014] The polymerizable monomers constituting the structural unit of the liquid crystal polymer in the present invention include, for example, aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic aminocarboxylic acid, aromatic hydroxyamine, aromatic diamine, aliphatic diol and aliphatic dicarboxylic acid.Such polymerizable monomers may be used alone or in combination of two or more polymerizable monomers.Preferably, at least one polymerizable monomer having a hydroxyl group and a carboxyl group is used.

[0015] The polymerizable monomer constituting the structural unit of the liquid crystal polymer may be an oligomer formed by bonding one or more of the above compounds, that is, an oligomer constituted by one or more of the above compounds.

[0016] Specific examples of aromatic hydroxycarboxylic acids include 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 2-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 7-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and their alkyl, alkoxy or halogen-substituted derivatives, as well as their acylated derivatives, ester derivatives, acid halides and other ester-forming derivatives. Among these, from the viewpoint of the heat resistance, mechanical strength and ease of adjusting the melting point of the resulting liquid crystal polymer, one or more compounds selected from the group consisting of 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are preferred.

[0017] Specific examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, 3,4'-dicarboxybiphenyl, and 4,4"-dicarboxyterphenyl, as well as their alkyl, alkoxy, or halogen-substituted derivatives and their ester derivatives, such as acid halides. Among these, from the viewpoint of effectively enhancing the heat resistance of the resulting liquid crystal polymer, one or more compounds selected from the group consisting of terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid are preferred, and terephthalic acid and 2,6-naphthalenedicarboxylic acid are more preferred.

[0018] Specific examples of aromatic diols include hydroquinone, resorcin, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and 2,2'-dihydroxybinaphthyl, their alkyl, alkoxy or halogen substitution products, and their acylated derivatives. Among these, from the viewpoint of excellent reactivity during polymerization, one or more compounds selected from the group consisting of hydroquinone, resorcin, 4,4'-dihydroxybiphenyl, and 2,6-dihydroxynaphthalene are preferred, and one or more compounds selected from the group consisting of hydroquinone, 4,4'-dihydroxybiphenyl, and 2,6-dihydroxynaphthalene are more preferred.

[0019] Specific examples of aromatic aminocarboxylic acids include 4-aminobenzoic acid, 3-aminobenzoic acid, 6-amino-2-naphthoic acid, alkyl, alkoxy or halogen substituted derivatives thereof, and ester-forming derivatives thereof such as acylation products, ester derivatives and acid halides.

[0020] Specific examples of aromatic hydroxyamines include 4-aminophenol, N-methyl-4-aminophenol, 3-aminophenol, 3-methyl-4-aminophenol, 4-amino-1-naphthol, 4-amino-4'-hydroxybiphenyl, 4-amino-4'-hydroxybiphenyl ether, 4-amino-4'-hydroxybiphenylmethane, 4-amino-4'-hydroxybiphenyl sulfide, and 2,2'-diaminobinaphthyl, their alkyl, alkoxy or halogen-substituted products, and their acylated products and other ester-forming derivatives. Among these, 4-aminophenol is preferred from the viewpoint of easily achieving a balance between the heat resistance and mechanical strength of the resulting liquid crystal polymer.

[0021] Specific examples of aromatic diamines include amide-forming derivatives such as 1,4-phenylenediamine, 1,3-phenylenediamine, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, alkyl, alkoxy or halogen-substituted derivatives thereof, and acylated derivatives thereof.

[0022] Specific examples of the aliphatic diol include ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and acylated products thereof. In addition, a polymer containing an aliphatic diol, such as polyethylene terephthalate or polybutylene terephthalate, may be reacted with the aromatic oxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, and their acylated products, ester derivatives, acid halides, etc.

[0023] Specific examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, fumaric acid, maleic acid, and hexahydroterephthalic acid. Among these, oxalic acid, succinic acid, adipic acid, suberic acid, sebacic acid, and dodecanedioic acid are preferred from the viewpoint of excellent reactivity during polymerization.

[0024] The polymerizable monomer forming the constitutional unit of the liquid crystal polymer in the present invention may contain, as other copolymerization components, dihydroxyterephthalic acid, 4-hydroxyisophthalic acid, 5-hydroxyisophthalic acid, trimellitic acid, 1,3,5-benzenetricarboxylic acid, pyromellitic acid, or their alkyl, alkoxy or halogen-substituted derivatives, as well as their acylated derivatives, ester derivatives, acid halides, and other ester-forming derivatives, within the scope of the present invention, without impairing the object of the present invention. The amount of these polymerizable monomers used is preferably 10 mol % or less based on the total constitutional units constituting the liquid crystal polymer.

[0025] In the present invention, the liquid crystal polymer may contain a thioester bond, provided that the object of the present invention is not impaired. Polymerizable monomers that provide such bonds include mercapto aromatic carboxylic acids, aromatic dithiols, and hydroxy aromatic thiols. The content of these polymerizable monomers is preferably 10 mol% or less based on the total constitutional units that constitute the liquid crystal polymer.

[0026] Polymers combining these repeating units include those that form an anisotropic molten phase and those that do not, depending on the monomer composition, composition ratio, and sequence distribution of each repeating unit in the polymer. However, the liquid crystal polymers used in the present invention are limited to those that form an anisotropic molten phase.

[0027] The liquid crystal polymer used in the present invention preferably has a crystalline melting temperature of 250 to 360°C, more preferably 260 to 350°C, and even more preferably 270 to 345°C, as measured by a differential scanning calorimeter.

[0028] In the present specification and claims, the "crystalline melting temperature" is determined from the crystalline melting temperature peak temperature when measured at a heating rate of 20°C / min using a differential scanning calorimeter (hereinafter abbreviated as DSC). More specifically, after observing the endothermic peak temperature (Tm1) observed when a liquid crystal polymer sample is measured under a heating condition of 20°C / min from room temperature, the sample is held at a temperature 20 to 50°C higher than Tm1 for 10 minutes, and then cooled to room temperature under a cooling condition of 20°C / min, and then measured again under a heating condition of 20°C / min. The temperature showing the peak top is taken as the crystalline melting temperature of the liquid crystal polymer. For example, Exstar6000 manufactured by Seiko Instruments Inc. can be used as a measuring instrument.

[0029] As the liquid crystal polymer used in the present invention, a liquid crystal polyester resin containing repeating units represented by formula (I) and formula (II) is preferably used because of its excellent fluidity and mechanical properties. [ka]

[0030] In one embodiment of the present invention, a liquid crystal polyester resin composed of repeating units represented by formula (I) and formula (II) is preferably used as the liquid crystal polymer. [ka]

[0031] In another embodiment of the present invention, a wholly aromatic liquid crystal polyester resin containing repeating units represented by formulae (I) to (IV) is preferably used as the liquid crystal polymer. [ka] [In the formula, Ar1 and Ar2 each represent a divalent aromatic group.]

[0032] Here, in the repeating units represented by formulas (III) to (IV), Ar1 and Ar2 are preferably each independently one or more repeating units selected from the aromatic groups represented by formulas (1) to (4). [ka]

[0033] One of the preferred embodiments of the liquid crystal polymer used in the present invention is a wholly aromatic liquid crystal polyester resin containing repeating units represented by the following formulas (A) to (D).

[0034] [ka] [In the formula, p, q, r and s represent the composition ratio (mol %) of each repeating unit in the liquid crystal polyester resin, and satisfy the following conditions: 60 ≤ p ≤ 80; 0.1≦q≦10; 10≦r≦20; 10≦s≦20]

[0035] In the wholly aromatic liquid crystal polyester resins containing the above formulae (A) to (D), the total composition ratio of the repeating units [p+q+r+s] is preferably 100 mol %, but other repeating units may be further contained as long as the object of the present invention is not impaired.

[0036] Another preferred embodiment of the liquid crystal polymer used in the present invention is a wholly aromatic liquid crystal polyester resin containing repeating units represented by the following formulas (E) to (I).

[0037] [ka] [In the formula, t, u, v, w and x represent the composition ratio (mol %) of each repeating unit in the liquid crystal polyester resin, and satisfy the following conditions: 25 ≤ t ≤ 45; 2≦u≦10; 10≦v≦20; 10≦w≦20; 20≦x≦40; v>w]

[0038] In the wholly aromatic liquid crystal polyester resins including the above formulae (E) to (I), the total composition ratio of the repeating units [t+u+v+w+x] is preferably 100 mol %, but other repeating units may be further contained as long as the object of the present invention is not impaired.

[0039] Another preferred embodiment of the liquid crystal polymer used in the present invention is a wholly aromatic liquid crystal polyester resin containing repeating units represented by the following formulae (J) and (K).

[0040] [ka] [In the formula, y and z each represent a composition ratio (mol %) of each repeating unit in the liquid crystal polyester resin, and satisfy the following condition: 60≦y≦80; 20≦z≦40]

[0041] In the wholly aromatic liquid crystal polyester resin containing the above formulae (J) and (K), the sum of the composition ratios of the repeating units [y+z] is preferably 100 mol %, but other repeating units may be further contained as long as the object of the present invention is not impaired.

[0042] The above liquid crystal polymers may be used alone or in combination of two or more liquid crystal polymers.

[0043] The method for producing the liquid crystal polymer used in the present invention will be described below.

[0044] The method for producing the liquid crystal polymer used in the present invention is not particularly limited, and the liquid crystal polymer can be obtained by subjecting a polymerizable monomer to a known polycondensation method for forming an ester bond or an amide bond, such as a molten acidolysis method or a slurry polymerization method.

[0045] The melt acidolysis method is a preferred method for preparing the liquid crystal polymer used in the liquid crystal polymer composition of the present invention. This method involves first heating the polymerizable monomers to form a molten solution of the reactants, and then continuing the polycondensation reaction to obtain a molten polymer. A vacuum may be applied to facilitate removal of volatile by-products (e.g., acetic acid, water, etc.) produced during the final stage of condensation.

[0046] A slurry polymerization process is a process in which polymerizable monomers are reacted in the presence of a heat exchange fluid, resulting in a solid product suspended in the heat exchange medium.

[0047] In either the molten acidolysis method or the slurry polymerization method, the polymerizable monomer used in producing the liquid crystal polymer can also be subjected to the reaction at room temperature in a modified form in which the hydroxyl group and / or amino group is acylated, i.e., a lower acylated product.

[0048] The lower acyl group preferably has 2 to 5 carbon atoms, more preferably 2 or 3. In a preferred embodiment of the present invention, an acetylated product of the polymerizable monomer is subjected to the reaction.

[0049] The lower acylated product of the polymerizable monomer may be a product previously synthesized by separate acylation, or may be produced in the reaction system by adding an acylating agent such as acetic anhydride to the polymerizable monomer during the production of the liquid crystal polymer.

[0050] In either the molten acidolysis method or the slurry polymerization method, the polycondensation reaction is carried out at a temperature of 150 to 400° C., preferably 250 to 370° C., under normal pressure and / or reduced pressure, and a catalyst may be used as necessary.

[0051] Specific examples of catalysts include organotin compounds such as dialkyltin oxides (e.g., dibutyltin oxide) and diaryltin oxides; titanium dioxide; antimony trioxide; organotitanium compounds such as alkoxytitanium silicates and titanium alkoxides; alkali and alkaline earth metal salts of carboxylic acids (e.g., sodium acetate, potassium acetate); and gaseous acid catalysts such as Lewis acids (e.g., boron trifluoride) and hydrogen halides (e.g., hydrogen chloride).

[0052] When a catalyst is used, the amount of the catalyst is preferably 1 to 1000 ppm, more preferably 2 to 100 ppm, based on the total amount of polymerizable monomers.

[0053] The liquid crystal polymer obtained by such a polycondensation reaction is usually discharged in a molten state from a polymerization reaction vessel, processed into pellets, flakes, or powder, and then melt-kneaded with other components.

[0054] The liquid crystal polyester in the form of pellets, flakes, or powder may be heat-treated in a substantially solid phase state under reduced pressure, vacuum, or an atmosphere of an inert gas such as nitrogen or helium, in order to increase the molecular weight and improve the heat resistance.

[0055] The glass-based filler contained in the liquid crystal polymer composition of the present invention is one or more types selected from the group consisting of glass spheres and glass fibers having an aspect ratio of 10 or less.

[0056] As the glass spheres, glass beads and glass balloons are preferred, and glass beads are particularly preferred because of their excellent heat shock resistance. The average particle size of the glass spheres is preferably from 1 to 100 μm, more preferably from 5 to 60 μm, and even more preferably from 10 to 30 μm. In the present invention, the "average particle size" of the glass spheres is the median size measured by a laser diffraction method. The glass spheres do not necessarily have to be completely spherical and may include elliptical ones, but it is preferable that the aspect ratio is 2 or less.

[0057] The glass fiber is not particularly limited as long as it has an aspect ratio of 10 or less, but chopped glass and milled glass are preferably used.

[0058] The glass fibers have a number average fiber length in the liquid crystal polymer composition of preferably 10 to 200 μm, more preferably 10 to 150 μm, and even more preferably 10 to 100 μm, and a number average fiber diameter of preferably 5 to 15 μm, and more preferably 6 to 12 μm.

[0059] In the fibrous glass-based filler (glass fiber), the aspect ratio, which is expressed by the number average fiber length / number average fiber diameter, is preferably 9 or less, more preferably 7 or less, and even more preferably 5 or less. If the aspect ratio exceeds 10, the effect of improving heat shock resistance becomes insufficient. The lower limit of the aspect ratio is preferably closer to 1 (cylindrical), but is usually 1.2.

[0060] The number average fiber diameter and number average fiber length of the fibrous glass filler can be measured by observing with a microscope. First, 1.0 g of the liquid crystal polyester resin composition is collected in a crucible, and in an electric furnace, it is treated at 500°C for 5 hours to be incinerated, and the residue is dispersed in methanol and spread on a slide glass to prepare a sample. Next, in the projected image of the glass fiber in the microscope field of view, the length in the longitudinal direction is read as the fiber length, and the length in the direction perpendicular to the longitudinal direction is read as the fiber diameter, and the arithmetic average value is calculated to obtain the value. The modulus of the average value is 200 or more.

[0061] The glass filler used in the present invention may be surface-treated with a silane coupling agent or the like.

[0062] The content of the glass-based filler is 10 to 60 parts by mass, preferably 12 to 59 parts by mass, more preferably 14 to 55 parts by mass, and further preferably 16 to 52 parts by mass, relative to 100 parts by mass of the liquid crystal polymer. If the content of the glass-based filler is less than 10 parts by mass, the effect of improving heat shock resistance becomes insufficient, and if it exceeds 60 parts by mass, the heat shock resistance and fluidity tend to decrease.

[0063] The liquid crystal polymer composition of the present invention further contains 0.5 to 25 parts by mass, preferably 1 to 23 parts by mass, more preferably 2 to 22 parts by mass, and further preferably 3 to 20 parts by mass of a functional group-containing polyolefin resin per 100 parts by mass of the liquid crystal polymer.

[0064] If the content of the functional group-containing polyolefin resin is less than 0.5 parts by mass, the heat shock resistance of the resulting liquid crystal polymer composition is not sufficiently improved, whereas if the content of the functional group-containing polyolefin resin is more than 20 parts by mass, the mechanical strength and flowability of the resulting liquid crystal polymer composition tend to decrease.

[0065] Specific examples of functional group-containing polyolefin-based resins include maleic anhydride grafted polyolefin-based copolymers, vinyl monomer / maleic anhydride copolymers, epoxy group-containing polyolefin-based copolymers, epoxy group-containing vinyl random, graft or block copolymers, carboxyl group-containing olefin random or graft copolymers, etc. Among these, copolymers having at least one functional group selected from the group consisting of acid anhydride groups, carboxyl groups and epoxy groups are preferred, and maleic anhydride grafted polyolefin-based copolymers and epoxy group-containing polyolefin-based copolymers are more preferred.

[0066] Specific examples of maleic anhydride grafted polyolefin copolymers include maleic anhydride grafted polypropylene (PP-g-MAH), maleic anhydride grafted ethylene / propylene rubber (EPR-g-MAH), and maleic anhydride grafted ethylene / propylene / diene rubber (EPDM-g-MAH).

[0067] Specific examples of vinyl monomer / maleic anhydride copolymers include styrene / maleic anhydride copolymers, styrene / (meth)acrylic acid / maleic anhydride copolymers, and (meth)acrylic acid ester / maleic anhydride copolymers.

[0068] Specific examples of epoxy group-containing polyolefin copolymers include ethylene / glycidyl (meth)acrylate copolymers, ethylene / glycidyl (meth)acrylate / vinyl acetate copolymers, ethylene / glycidyl (meth)acrylate / methyl (meth)acrylate copolymers, ethylene / glycidyl (meth)acrylate / ethyl (meth)acrylate copolymers, polystyrene graft copolymers onto ethylene / glycidyl (meth)acrylate copolymers (EGMA or EGA-g-PS), polymethyl (meth)acrylate graft copolymers onto ethylene / glycidyl (meth)acrylate copolymers (EGMA or EGA-g-PMMA), and styrene / acrylonitrile graft copolymers onto ethylene / glycidyl (meth)acrylate copolymers (EGMA or EGA-g-AS).

[0069] Specific examples of epoxy group-containing vinyl random, graft or block copolymers include glycidyl methacrylate grafted polystyrene (PS-g-GMA), glycidyl methacrylate grafted polymethyl methacrylate (PMMA-g-GMA), glycidyl methacrylate grafted polyacrylonitrile (PAN-g-GMA), etc.

[0070] Specific examples of carboxyl group-containing olefin random or graft copolymers include carboxylated polyethylene, carboxylated polypropylene, ethylene / (meth)acrylic acid copolymers (ionomers), and styrene / (meth)acrylic acid copolymers.

[0071] As the functional group-containing polyolefin resin contained in the liquid crystal polymer composition of the present invention, a maleic anhydride grafted polypropylene copolymer and / or an ethylene / glycidyl (meth)acrylate copolymer are preferred.

[0072] The above-mentioned functional group-containing polyolefin resins may be used alone or in combination of two or more kinds.

[0073] The liquid crystal polymer composition of the present invention may further contain a plate-like filler. Examples of the plate-like filler that may be further contained include talc, mica, kaolin, clay, vermiculite, feldspar powder, acid clay, rosewood clay, sericite, sillimanite, bentonite, glass flakes, slate powder, silicate such as silane, carbonate such as calcium carbonate, chalk, barium carbonate, magnesium carbonate, dolomite, barite powder, precipitated calcium sulfate, calcined gypsum, sulfate such as barium sulfate, hydroxide such as hydrated alumina, oxide such as alumina, antimony oxide, magnesia, zinc oxide, silica, silica sand, quartz, white carbon, diatomaceous earth, sulfide such as molybdenum disulfide, plate-like wollastonite, etc., which can be used alone or in combination of two or more. Among these plate-like fillers, talc and / or mica are preferred in terms of excellent dimensional stability.

[0074] The content of the plate-like filler is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 10 to 30 parts by mass, based on 100 parts by mass of the liquid crystal polymer.

[0075] The liquid crystal polymer composition of the present invention may further contain other resin components within the scope of the present invention. Examples of the other resin components include thermoplastic resins such as polyamide, polyester, polyacetal, polyphenylene ether and its modified products, polysulfone, polyethersulfone, polyetherimide, and polyamideimide, and thermosetting resins such as phenol resin, epoxy resin, and polyimide resin.

[0076] The other resin components may be contained alone or in combination of two or more kinds. The content of the other resin components is not particularly limited, and may be appropriately determined according to the use and purpose of the liquid crystal polymer composition. Typically, the total content of the other resins is preferably added in a range of 0.1 to 100 parts by mass, more preferably 0.2 to 80 parts by mass, relative to 100 parts by mass of the liquid crystal polymer.

[0077] The liquid crystal polymer composition of the present invention may contain additives other than those mentioned above, provided that the effects of the present invention are not impaired.

[0078] Examples of other additives include lubricants such as higher fatty acids, higher fatty acid esters, higher fatty acid amides, higher fatty acid metal salts (here, higher fatty acids refer to, for example, those having 10 to 25 carbon atoms), and fluorocarbon surfactants; release improvers such as polysiloxanes and fluororesins; colorants such as dyes, pigments, and carbon black; flame retardants, antistatic agents, surfactants, antioxidants such as phosphorus-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants; weathering agents, heat stabilizers, and neutralizers. Additives having an external lubricant effect, such as higher fatty acids, higher fatty acid esters, higher fatty acid metal salts, and fluorocarbon surfactants, may be attached to the surface of the pellets of the liquid crystal polymer composition in advance when molding the liquid crystal polymer composition. These additives may be used alone or in combination of two or more.

[0079] The content of these other additives is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the liquid crystal polymer. If the content of these other additives exceeds the upper limit, molding processability and thermal stability tend to decrease.

[0080] The liquid crystal polymer composition of the present invention can be prepared by blending a liquid crystal polymer, a glass-based filler, and a functional group-containing olefin resin, and optionally a plate-like filler, other additives, other resin components, etc. in a predetermined composition, and melt-kneading the mixture using a Banbury mixer, a kneader, a single-screw or twin-screw extruder, etc.

[0081] The liquid crystal polymer composition of the present invention has excellent heat shock resistance while retaining the properties of liquid crystal polymers such as mechanical strength and fluidity.

[0082] In the liquid crystal polymer composition of the present invention, the tensile strength is preferably 70 to 170 MPa, more preferably 80 to 160 MPa, as measured in accordance with ASTM D638 using an ASTM No. 4 dumbbell test piece having a thickness of 3.2 mm.

[0083] The liquid crystal polymer composition of the present invention has a tensile modulus of preferably 4.5 to 10.5 GPa, more preferably 5.0 to 10.0 GPa, as measured in accordance with ASTM D638 using an ASTM No. 4 dumbbell test piece having a thickness of 3.2 mm.

[0084] The liquid crystal polymer composition of the present invention preferably has a tensile elongation of 3.0 to 7.5%, more preferably 3.5 to 7.0%, when measured in accordance with ASTM D638 using an ASTM No. 4 dumbbell test piece having a thickness of 3.2 mm.

[0085] In the liquid crystal polymer composition of the present invention, the ratio of tensile elongation / tensile modulus is 0.6 or more, preferably 0.65 or more, more preferably 0.7 or more, and even more preferably 0.75 or more. If the ratio of tensile elongation / tensile modulus is less than 0.60, the heat shock resistance tends to be insufficient. The upper limit of the tensile elongation / tensile modulus is usually 1.5.

[0086] Tensile elongation indicates the ductility of a material, with a larger value indicating that the material is more easily stretched. Tensile modulus is expressed as the ratio of tensile stress per unit cross-sectional area to the strain generated in the stress direction, with a smaller value indicating that the material is softer and has a larger stress-strain. In the present invention, it is presumed that a large ratio of tensile elongation / tensile modulus in the liquid crystal polymer composition leads to an excellent balance between ductility and stress-strain, resulting in an improved effect on heat shock resistance during temperature changes.

[0087] The liquid crystal polymer composition of the present invention preferably has a flexural strength of 80 to 165 MPa, more preferably 85 to 160 MPa, in a bending test using an ASTM No. 4 bending test piece having a thickness of 3.2 mm.

[0088] The liquid crystal polymer composition of the present invention has a flexural modulus of preferably 3.5 to 9.0 GPa, more preferably 4.0 to 8.5 GPa, in a bending test using an ASTM No. 4 bending test piece having a thickness of 3.2 mm.

[0089] The liquid crystal polymer composition of the present invention thus obtained can be molded or processed by a known molding method using an injection molding machine, an extruder, etc. to obtain a desired molded product. The molded products are preferably used for electrical and electronic products such as connectors, switches, relays, capacitors, coils, transformers, and antennas.

[0090] Since the liquid crystal polymer composition of the present invention has excellent heat shock resistance, it is particularly suitable for use in insert molded articles. The insert molded article contains the liquid crystal polymer composition of the present invention and a metal, and can be produced by insert molding. EXAMPLES

[0091] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples. In the examples, the crystal melting temperature, bending strength, bending modulus, tensile strength, tensile modulus, tensile elongation and heat shock resistance were evaluated by the methods described below.

[0092] <Crystal Melting Temperature> Measurement was performed using a differential scanning calorimeter (DSC7020 manufactured by Hitachi High-Tech Science Corporation). The resin samples of the following examples and comparative examples were measured under conditions of a temperature rise of 20°C / min from room temperature, and after observing the endothermic peak temperature (Tm1), the sample was held at a temperature 20 to 50°C higher than Tm1 for 10 minutes. Next, the sample was cooled to room temperature under a temperature drop condition of 20°C / min, and then measured again under a temperature rise condition of 20°C / min to observe the endothermic peak, and the temperature showing the peak top was taken as the crystalline melting temperature of the resin sample.

[0093] <Tensile strength, tensile modulus, tensile elongation> Using an injection molding machine (UH1000-110 manufactured by Nissei Plastic Industrial Co., Ltd.), the material was injection molded at a cylinder temperature of 20 to 40°C above the crystal melting temperature and a mold temperature of 70°C to obtain dumbbell-shaped tensile test pieces (ASTM No. 4, thickness 3.2 mm). The tensile test was performed using an autograph AG-X plus manufactured by Shimadzu Corporation in accordance with ASTM D638, with a span distance of 64.0 mm and a tensile speed of 5 mm / min.

[0094] <Flexural strength, flexural modulus> Using an injection molding machine (UH1000-110 manufactured by Nissei Plastics Co., Ltd.), injection molding was performed at a cylinder temperature of 20 to 40°C above the crystal melting temperature and a mold temperature of 70°C to obtain rectangular bending test pieces (length 127 mm x width 12.7 mm x thickness 3.2 mm). The bending test was a three-point bending test using an autograph AGX-V manufactured by Shimadzu Corporation in accordance with ASTM D790, with a span distance of 50.0 mm and a compression speed of 1.3 mm / min.

[0095] <Heat shock resistance (production and evaluation of insert moldings)> Figure 1 shows the insert member used in the evaluation of heat shock resistance. The insert member 1 is made of an aluminum alloy, and has a cylindrical portion 2 (diameter 25 mm × height 20 mm) and a protrusion 3 (height 20 mm) provided on the upper portion of the cylindrical portion 2.

[0096] The protrusion 3 has a teardrop shape when viewed from the top, and the tip 4 and the back surface 5 (the position furthest from the tip 4 ) are in contact with the circumferential portion 6 of the cylindrical portion 2 . This insert member 1 was attached to a mold, and a resin composition was injected into the mold at a cylinder temperature of 300° C., a mold temperature of 50° C., an injection time of 5.0 seconds, and a cooling time of 8.0 seconds to produce the insert molded body 7 shown in FIG.

[0097] The insert molded body 7 is molded by surrounding the projection 3 of the insert member 1 with a resin member 8, and by positioning a weld portion 9 at the tip portion 4 of the projection 3. The diameter of the insert molded body is 30 mm, and the thickness of the weld portion 9 is 1 mm. Five insert moldings of each type were produced and the heat shock resistance was evaluated by the following test method.

[0098] Test 1 The insert molded body was subjected to a heat shock resistance test for five cycles, in which one cycle was heating at 150°C in a high-temperature oven for one hour and then cooling in a room at 23°C for one hour. If one or more molded bodies had cracks in the welds, the test was marked as "X."

[0099] Test 2 The insert moldings that were not marked as "X" in the above test 1 were subjected to five cycles of a heat shock resistance test, in which one cycle was heating at 150°C for one hour in a high-temperature oven, followed by cooling in a -20°C freezer for one hour. If one or more moldings had cracks in the weld, they were marked as "△".

[0100] Test 3 The insert molded articles that were not graded as "△" in the above test 2 were subjected to five cycles of a heat shock resistance test, in which one cycle was heating at 180°C for one hour in a high-temperature oven, followed by cooling in a -20°C freezer for one hour. If one or more molded articles showed cracks in the welds, they were given a grade of "O", and those that showed no cracks were given a grade of "◎".

[0101] In the examples and comparative examples, the following abbreviations represent the following compounds. POB: Parahydroxybenzoic acid BON6: 6-hydroxy-2-naphthoic acid HQ: Hydroquinone BP: 4,4'-dihydroxybiphenyl TPA: Terephthalic acid NDA: 2,6-naphthalenedicarboxylic acid

[0102] [Synthesis Example 1 (LCP1)] In a reaction vessel equipped with a stirrer with a torque meter and a distillation tube, POB and BON6 were charged in a total amount of 6.5 moles in the composition ratio shown in Table 1, and acetic anhydride was further charged in an amount of 1.03 times the moles of the hydroxyl groups (moles) of all monomers, and deacetic acid polymerization was carried out under the following conditions.

[0103] [Table 1]

[0104] The temperature was raised from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere, and the temperature was maintained for 30 minutes. Next, the temperature was raised to 350°C over 7 hours while distilling off the by-product acetic acid, and then the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when a predetermined torque was reached, and the contents of the reaction vessel were removed and crushed to obtain pellets of liquid crystal polyester resin. The amount of acetic acid distilled during polymerization was almost the theoretical value. The crystal melting temperature (Tm) of the obtained pellets was 280°C.

[0105] [Synthesis example 2 (LCP2)] In a reaction vessel equipped with a stirrer with a torque meter and a distillation tube, POB, BON6, HQ, BP and TPA were charged in a total amount of 6.5 moles in the composition ratio shown in Table 2, and acetic anhydride was further charged in an amount of 1.02 times the moles of the hydroxyl groups (moles) of all monomers, and deacetic acid polymerization was carried out under the following conditions.

[0106] [Table 2]

[0107] The temperature was raised from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere, and the temperature was maintained for 30 minutes. Next, the temperature was raised to 350°C over 7 hours while distilling off the by-product acetic acid, and then the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when a predetermined torque was reached, and the contents of the reaction vessel were removed and crushed to obtain pellets of liquid crystal polyester resin. The amount of acetic acid distilled during polymerization was almost the theoretical value. The crystal melting temperature (Tm) of the obtained pellets was 321°C.

[0108] [Synthesis Example 3 (LCP3)] In a reaction vessel equipped with a stirrer with a torque meter and a distillation tube, POB, BON6, HQ and NDA were charged in a total amount of 6.5 moles in the composition ratio shown in Table 3, and acetic anhydride was further charged in an amount of 1.03 times the moles of the hydroxyl groups (moles) of all monomers, and deacetic acid polymerization was carried out under the following conditions.

[0109] [Table 3]

[0110] The temperature was raised from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere, and the temperature was maintained for 30 minutes. Next, the temperature was raised to 350°C over 7 hours while distilling off the by-product acetic acid, and then the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when a predetermined torque was reached, and the contents of the reaction vessel were taken out and crushed to obtain pellets of liquid crystal polyester resin. The amount of acetic acid distilled during polymerization was almost the theoretical value. The crystal melting temperature (Tm) of the obtained pellets was 335°C.

[0111] The fillers used in the following examples and comparative examples are shown below.

[0112] [Glass-based filler] Glass spheres: Potters Barotini glass beads EGB731B-PN (average particle size: 20 μm, aspect ratio: 1) Glass fiber 1: Milled glass fiber PFE-001 (average fiber diameter: 10 μm) manufactured by Nitto Boseki Co., Ltd. Glass fiber 2: Milled glass fiber EPH80M-01N (average fiber diameter: 10 μm) manufactured by Nippon Electric Glass Co., Ltd. Glass fiber 3: Chopped glass fiber ECS03T-747H / PW (average fiber diameter: 10 μm) manufactured by Nippon Electric Glass Co., Ltd. Glass fiber 4: Chopped glass fiber ECS03T-747H / PW (average fiber diameter: 10 μm) manufactured by Nippon Electric Glass Co., Ltd.

[0113] For glass fibers 1 to 4, the aspect ratios in the liquid crystal polymer composition were adjusted to the following values ​​by changing the feeding positions to the twin-screw extruder and the kneading time. The aspect ratios were calculated by measuring the number average fiber length and number average fiber diameter by the above-mentioned method. Glass fiber 1 (aspect ratio: 4) Glass fiber 2 (aspect ratio: 8) Glass fiber 3 (aspect ratio: 10) Glass fiber 4 (aspect ratio: 30)

[0114] [Functional group-containing olefin resin] BF1: Bondfast BF-2C (ethylene-glycidyl methacrylate copolymer, containing 6% by mass of glycidyl methacrylate) manufactured by Sumitomo Chemical Co., Ltd. BF2: Bondfast BF-7M manufactured by Sumitomo Chemical Co., Ltd. (ethylene-glycidyl methacrylate-methyl acrylate copolymer, containing 6% by mass of glycidyl methacrylate and 27% by mass of methyl acrylate) BF3: Bondfast CG5001 (ethylene-glycidyl methacrylate copolymer, containing 19% by mass of glycidyl methacrylate) manufactured by Sumitomo Chemical Co., Ltd. BF4: Bondfast VC40 (glycidyl group-containing copolyester) manufactured by Sumitomo Chemical Co., Ltd.

[0115] [Plate-shaped filler] Talc: talc "RL119" manufactured by Fuji Talc Kogyo Co., Ltd. (average particle size: 17 μm) Mica: Yamaguchi Mica Co., Ltd. "AB-25S" (average particle size: 24 μm)

[0116] Examples 1 to 18 and Comparative Examples 1 to 12 The LCPs, glass-based fillers, functional group-containing olefin resins, and plate-like fillers synthesized in Synthesis Examples 1 to 3 were mixed to the contents (parts by mass) shown in Tables 4 to 6, and melt-kneaded at 350°C using a twin-screw extruder (TEX-30, manufactured by Nippon Steel Corporation) to obtain pellets of a liquid crystal polymer composition. The tensile strength, tensile modulus, tensile elongation, flexural strength, flexural modulus, and heat shock resistance were evaluated by the above-mentioned methods. The results are shown in Tables 4 to 6.

[0117] As shown in Tables 4 to 6, it can be seen that a liquid crystal polymer composition containing a specific glass-based filler and a functional group-containing olefin resin in a specified ratio and having a tensile elongation / tensile modulus ratio of 0.6 or more has improved heat shock resistance.

[0118] [Table 4]

[0119] [Table 5]

[0120] [Table 6] [Explanation of symbols]

[0121] 1 Insert material 2 Cylinder section 3 Protrusion 4 Tip 5 Back part 6 Circumference 7 Insert molding 8 Resin parts 9 Weld

Claims

1. A liquid crystal polymer composition comprising 100 parts by mass of a liquid crystal polymer, 10 to 60 parts by mass of a glass-based filler, and 0.5 to 25 parts by mass of a functional group-containing olefin-based resin, wherein the glass-based filler is at least one type selected from the group consisting of glass spheres and glass fibers having an aspect ratio of 10 or less, and wherein the ratio of tensile elongation / tensile modulus of elasticity is 0.6 or more.

2. The liquid crystal polymer is represented by the formula (I) and the formula (II): 【Chemistry 1】 2. The liquid crystal polymer composition according to claim 1, which is a liquid crystal polyester resin containing a repeating unit represented by the following formula:

3. The liquid crystal polymer is represented by the formula (I) and the formula (II): 【Chemistry 2】 2. The liquid crystal polymer composition according to claim 1, which is a liquid crystal polyester resin composed of a repeating unit represented by the following formula:

4. The liquid crystal polymer is represented by the formula (I) to the formula (IV): 【Chemistry 3】 [In the formula, Ar 1 and Ar 2 each represents a divalent aromatic group.

2. The liquid crystal polymer composition according to claim 1, which is a wholly aromatic liquid crystal polyester resin containing a repeating unit represented by the following formula:

5. The repeating units represented by formulae (III) to (IV) are Ar 1 and Ar 2 are each independently represented by the formulas (1) to (4). 【Chemistry 4】 The liquid crystal polymer composition according to claim 4, wherein each repeating unit is one or more kinds of repeating units selected from aromatic groups represented by the following formula:

6. The repeating unit represented by formula (III) is Ar 1 is a repeating unit represented by formula (1), and the repeating unit represented by formula (IV) is 2 The liquid crystal polymer composition according to claim 5 , wherein R 1 is a repeating unit which is an aromatic group represented by formula (1) and / or R 2 is a repeating unit which is an aromatic group represented by formula (3).

7. 2. The liquid crystalline polymer composition of claim 1, wherein the glass spheres are glass beads and / or glass balloons.

8. 2. The liquid crystalline polymer composition of claim 1, wherein the tensile elongation is 3.0 to 7.5%.

9. 2. The liquid crystalline polymer composition according to claim 1, having a tensile modulus of elasticity of 4.5 to 10.5 GPa.

10. The liquid crystal polymer composition according to claim 1, further comprising 1 to 50 parts by mass of a plate-like filler.

11. The liquid crystalline polymer composition of claim 10, wherein the platelet-like filler is mica and / or talc.

12. A molded article made of the liquid crystal polymer composition according to any one of claims 1 to 11.

13. The molded article according to claim 12, which is a part constituting one type selected from the group consisting of a connector, a switch, a relay, a capacitor, a coil, a transformer, and an antenna.

14. An insert molding comprising the liquid crystal polymer composition according to any one of claims 1 to 11 and a metal.

Citation Information

Patent Citations

  • Color synthesis optical system component resin composition and color synthesis optical system component obtained from the same

    JP2006083239A